化粧品原料の皮膚一次刺激性試験法の比較研究 モルモットに対する皮内注射 - ITOH Katsutoshi; SHIBAMOTO Akio; OKAMOTO Kikuhiko; 中村 和博; NAGURA Toshiaki; 市川 秀之 (Skin research, 1984)
As the test method for cosmetic materials safty evaluation. guinea pig intradermal injection was studied. Test materials were propylene glycol, 1. 3-butylene glycol, glycerin, pristane, liquid paraffin, squalane. This study was done in 3 different research laboratories of cosmetic companies. We performed this test with the same procedure in each laboratory.The results were as follows:(1) In polyols. only 30% concentration reacted. The positive rate order of polyols was 1. 3-butylene glycol≥propylene glycol, glycerin.(2) In hydrocarbons, the positive rate order was pristane>liquid paraffin≥squalane. 皮膚一次刺激性試験法の比較研究の一環として, 主に化粧品原料基準収載品目を用いてモルモットにおける皮内注射試験法を検討した。多価アルコールではいずれも30%濃度のみが反応を示し, その強度は1, 3-ブチレングリコール≧プロピレングリコール, グリセリンの順であった。炭化水素では比較的低濃度から反応が現われ, その強度はプリスタン>流動パラフィン#72≧スクワランの順であった。全試料申プリスタンが最も強い反応と強い反応持続性を示した。尚一部成績に実施施設間のバラツキが見られたが, 反応の強さの傾向はほぼ一致していた。皮内注射試験の意義について言及した。